(untitled) (Nepalese Journal of Development and Rural Studies, 2018)
Government of Nepal has declared irrigation as one of the leading programs for the agriculture development. Though Nepal has abundant water resources, water available for sound irrigation is still scarce. In the absence of well-organized water governance mechanisms, adequacy, fairness and reliability of water and sustainability of operation and maintenance, crop productivity remain low. This is not properly happening as most of the farmers have inadequate irrigation, inputs, technology, low education status, subsistence oriented farming, marginal farmers, low farm income, low purchasing power and poor health. The crop cultivation more than one time in a year has its positive relationship with cropping intensity and vice versa in the study area. Hence, households need to be getting up and encouraged towards year round irrigation that produce different types of the crops in different seasons and ultimately backs up in cropping intensity as well as productivity. The crop production is fluctuated widely as a result of the amount of water available as well as weather conditions. Despite the higher yield of spring paddy, the cropped area is constrained due to limit water availability in spring season.